Quality Evaluation of Balinese Bull’s Spermatozoa in Tris Egg Yolk Extender Supplemented with Java Turmeric Extract During Pre and Post-Thawing - Adawiyah, Robiatul; Rahayu, Sri; Marhendra, Agung PW; Fitriantini, Yeni (Biotropika: Journal of Tropical Biology, 2025)
Cryopreservation may induce oxidative stress that negatively affects spermatozoa quality. Supplementing semen extenders with antioxidants has emerged as an effective approach to minimise such detrimental effects. This research aims to analyse the effect of supplementing Java turmeric (Curcuma xanthorrhiza) rhizome extract (ERT) to a Tris egg yolk (TEY) extender on the cryopreserved sperm quality of Balinese bulls. Four treatment groups were evaluated: P0 (TEY+ 0% ERT) as control, P1 (TEY + 2% ERT), P2 (TEY + 4% ERT), and P3 (TEY + 6% ERT). The study encompassed the preparation of extenders, semen collection, spermatozoa quality observation in fresh, liquid, and frozen semen, also statistical analysis using one-way ANOVA followed by Duncan’s test at a 5% significance threshold. Progressive motility was assessed using CASA IVOS II, while viability and abnormalities were evaluated using eosin-nigrosin staining. The results showed that in pre-thawing conditions, all treatments had no significant difference compared to the control for all parameters. In post-thawing conditions, P1 maintained spermatozoa motility and viability similar to the control group. Moreover, the proportion of abnormal spermatozoa decreased significantly with higher ERT concentrations, with P3 exhibiting the lowest abnormality rate. These findings indicate that ERT supplementation in TEY extender can maintain motility and viability comparable to the control, while offering superior protection against post-thaw abnormalities.